Histochemical and morphometric characteristics of muscle fibres: breeds and muscles comparison - G. Toscano Pagano; C. Lazzaroni (Italian Journal of Animal Science, 2011)
Fibres histochemical characteristics seem affect the meat quality obtained from the skeletal muscles. In fact, the red fibres metabolise and store more lipid than the white ones (Ashmore et al., 1972), so important meat characteristics could be influenced by the muscle fibre type, as recently investigated (Morita et al., 2000; Ozawa et al., 2000; Vestergaard et al., 2000a, 2000b)....